Nephrin Signaling in the Podocyte: An Updated View of Signal Regulation at the Slit Diaphragm and Beyond - Martin, Claire E.; Jones, Nina (Frontiers in Endocrinology, 2018)
Podocytes are a major component of the glomerular blood filtration barrier, and alterations to the morphology of their unique actin-based foot processes are a common feature of kidney disease. Adjacent foot processes are connected by a specialized intercellular junction known as the slit diaphragm (SD), which serves as the ultimate barrier to regulate passage of macromolecules from the blood. While the link between SD dysfunction and reduced filtration selectivity has been recognized for nearly 50 years, our understanding of the underlying molecular circuitry began only 20 years ago, sparked by the identification of NPHS1, encoding the transmembrane protein nephrin. Nephrin not only functions as the core component of the extracellular SD filtration network, but also as a signaling scaffold via interactions at its short intracellular region. Phospho-regulation of several conserved tyrosine residues in this region influences signal transduction pathways which control podocyte cell adhesion, shape and survival, and emerging studies highlight roles for nephrin phospho-dynamics in mechanotransduction and endocytosis. The following review aims to summarize the last 5 years of advancement in our knowledge of how signaling centered at nephrin directs SD barrier formation and function. We further provide insight on promising frontiers in podocyte biology, which have implications for SD signaling in the healthy and diseased kidney.